Membangun Jiwa Entrepreneur Siswa Melalui Pelatihan Kewirausahaan di SMK Islam Al Fajar - Tasia, Fanni Erda; hamda, Nasmal; Nurhasanah, Enok (Pekodimas : Jurnal Pengabdian Kepada Masyarakat, 2025)
This community engagement initiative aims to cultivate and strengthen entrepreneurial mindsets among students of SMK Islam Al-Fajar through a structured and application-oriented entrepreneurship training program. The program is motivated by the urgent need to equip vocational school students with entrepreneurial competencies, enabling them to either enter the labor market with confidence or establish independent business ventures upon graduation. The implementation strategy encompassed a series of activities, including awareness sessions, theoretical and practical training, group discussions, and mentorship in developing basic business plans. The outcomes indicate a significant improvement in students’ enthusiasm, self-confidence, and ability to identify entrepreneurial opportunities within their local environment. Moreover, participants demonstrated enhanced comprehension of fundamental entrepreneurial principles, such as small business management, marketing strategies, and basic financial planning. In conclusion, the training program effectively encouraged creative and innovative thinking among students, laying the groundwork for the development of entrepreneurial character. It is recommended that such initiatives be sustained through strategic collaboration between schools, industry stakeholders, and higher education institutions. Keywords: entrepreneurship, entrepreneurial mindset, training program